"Should I Also Make a Garden Out of the Desert?": Camus' Story of Janine. (3rd July 2017) - Rohde-Brown, Juliet
Abstract : This article explores Albert Camus' short story "The Adulterous Woman" as a nature-based initiation into deeper complexity. Rich with archetypal and alchemical imagery, we are taken through a day in the life of Janine, where we can see, reflected in her experience, those places that beckon to greater authenticity within ourselves. The image of the desert invites us to consider, for Janine, the same kinds of questions that Jung asked in The Red Book : "Why is my self a desert? Have I lived too much outside of myself in men and events? Why did I avoid my self? Was I not dear to myself? But I have avoided the place of my soul" (2009, par. 72).